APLIKASI KAHOOT PADA PEMBELAJARAN MATEMATIKA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Syf. Rizekia Zulaikha Assegaf; Widya Susanti, Neti Esi, Ahmad Yani (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Mathematics learning using the Kahoot application as an evaluation material for mathematics learning is a technology-based learning system. Kahoot is a game-based learning platform, which is often used as educational technology-based learning. This platform is learning in the form of quizzes with answer choices. Kahoot can also make students learn math fun and not boring, so that students' thoughts about difficult and boring math can be broken. The Kahoot application is very helpful for teachers in building creativity and innovation in mathematics learning media that can be introduced to students in applying technology-based learning models easily and correctly. research and development methods (Research and Development). This game-based learning makes students more interested and increases the average score of students, as well as builds creativity and reasoning and makes students more active.